Comparative Analysis of GDM2000, WGS84, and MRT68 Coordinate Reference Systems based on Different Converter Modules - Hussaini, Alhaji; Tang Kang Wee, Kelvin; Izzati Abdul Hamid, Amalina; Abubakar, Auwal Graba; Tan, Chee Wee (Engineering, Technology & Applied Science Research, 2024)
The employment of multiple data and coordinate systems in Malaysia has not only resulted in challenges in surveying and mapping purposes but has also caused data compatibility issues with the local positioning system. This study examines the disparities in coordinates converted from the localized Geocentric Datum of Malaysia 2000 (GDM2000) to the global coordinate system, the World Geodetic System 1984 (WGS84), and from GDM2000 to the Malayan Revised Triangulation 1968 (MRT68). Several coordinate converter tools, available in the mCOORD mobile app, Geodetic Datum Transformation System (GDTS), Global Mapper, and Quantum GIS (QGIS), were employed to analyze the variation between converted coordinates. The locally developed coordinate converter tools, mCOORD and GDTS, exhibit similar levels of accuracy and conform to the standards set by the local survey department. In contrast, the reliability of the coordinate conversion tools in Global Mapper and QGIS seems uncertain. It is recommended that each data revision should establish transparency to the latest geodetic reference frame, with publicly accessible transformation parameters.